Price, Quality, Innovation, and Packaging Drive Consumer Purchase Behavior: Harga, Kualitas, Inovasi, dan Kemasan Mempengaruhi Perilaku Pembelian Konsumen - Fery Nurmansyah Ardianto; Minto Waluyo (Academia Open, 2025)
Background: In the competitive energy drink market, understanding consumer behavior is vital for sustaining brand performance. Kratingdaeng, a prominent brand in this sector, faces growing pressure to optimize marketing elements that drive consumer loyalty. Specific Background: Prior studies have explored isolated effects of price or product quality, yet comprehensive assessments integrating multiple marketing variables remain limited. Knowledge Gap: There is a lack of integrated empirical analysis on how price, product quality, innovation, and packaging design collectively affect both initial purchase decisions and repurchase behavior, especially in the Indonesian urban context. Aim: This study investigates the simultaneous effects of price, product quality, product innovation, and packaging design on purchase and repurchase decisions among Kratingdaeng consumers in Surabaya. Results: Using Structural Equation Modeling with AMOS 30 on data from 110 purposively sampled respondents, all four variables showed significant positive impacts on both purchase and repurchase decisions, with price and packaging design being the most influential. Novelty: This study integrates four critical marketing constructs within a single model, providing empirical evidence of their joint influence on consumer loyalty in the energy drink segment. Implications: The findings underscore the need for companies to harmonize pricing strategies, maintain product quality, innovate continuously, and invest in impactful packaging to enhance market retention and competitive advantage. Highlights: Highlights the combined impact of marketing elements on purchase and repurchase. Identifies packaging and price as dominant consumer decision drivers. Offers strategic insights to boost loyalty in the energy drink market. Keywords: Price, Product Quality, Product Innovation, Packaging Design, Consumer Behavior